Chronic inflammation and risk of colorectal and other obesity‐related cancers: The health, aging and body composition study. Issue 5 (19th October 2015) - Izano, Monika; Wei, Esther K.; Tai, Caroline; Swede, Helen; Gregorich, Steven; Harris, Tamara B.; Klepin, Heidi; Satterfield, Suzanne; Murphy, Rachel; Newman, Anne B.; Rubin, Susan M.; Braithwaite, Dejana; et al.
Abstract : Evidence of the association between chronic inflammation and the risk of colorectal cancer (CRC) and other obesity‐related cancers (OBRC) remains inconsistent, possibly due to a paucity of studies examining repeated measures of inflammation. In the Health ABC prospective study of 2, 490 adults aged 70–79 years at baseline, we assessed whether circulating levels of three markers of systemic inflammation, IL‐6, CRP and TNF‐α, were associated with the risk of CRC and OBRC, a cluster including cancers of pancreas, prostate, breast and endometrium. Inflammatory markers were measured in stored fasting blood samples. While only baseline measures of TNF‐α were available, IL‐6 and CRP were additionally measured at Years 2, 4, 6 and 8. Multivariable Cox models were fit to determine whether tertiles and log‐transformed baseline, updated and averaged measures of CRP and IL‐6 and baseline measures of TNF‐α were associated with the risk of incident cancer(s). During a median follow‐up of 11.9 years, we observed 55 and 172 cases of CRC and OBRC, respectively. The hazard of CRC in the highest tertile of updated CRP was more than double that in the lowest tertile (HR = 2.29; 95% CI: 1.08–4.86). No significant associations were seen between colorectal cancer and IL‐6 or TNF‐α. Additionally, no significant associations were found between obesity‐related cancers and the three inflammatory markers overall, but we observed a suggestion of effect modification by BMI and NSAID use. In summary, in this population, higher CRP levels were associated with increased risk of CRC, but not of OBRC. The findings provide new evidence that chronically elevated levels of CRP, as reflected by repeated measures of this marker, may play a role in colorectal carcinogenesis in older adults. Abstract : What's new? The relationship between chronic inflammation and cancer remains unclear partly due to the lack of repeated measurements of inflammatory markers prior to the onset of the disease. Here the authors evaluated repeated measurements of C‐reactive protein (CRP), TNF‐alpha and IL‐6 in blood of elderly adults participating in the Health ABC prospective study. They found a positive association with colorectal cancer, but not other obesity‐related cancers, with high CRP levels, supporting the hypothesis that chronically elevated levels of CRP may contribute to colorectal carcinogenesis.